Efficacy of Nano Silver Fluoride and/or Diode Laser In Enhancing Enamel Anticariogenicity around orthodontic brackets - Aya Anwar Alsherif; Mohamed Ali Farag; Mai Badreldin Helal (Nature Publishing Group, 2023)
Abstract Purpose This in vitro study aimed to compare the anticariogenic effect of using diode laser irradiation and/or nano silver fluoride varnish around orthodontic brackets. Materials and methods 60 caries-free and intact premolars were randomly divided into 3 experimental groups as follow: (1) Group I (nano silver fluoride treated group, n = 20), (2) Group II (diode laser treated group, n = 20) and (3) Group III (combined nano silver fluoride and diode laser treated group, n = 20). Anticariogenicity was assessed using polarized light, scanning electron microscope, elemental and shear bond strength analyses. Results PLM and SEM showed presence of few demineralized areas in group I. Group II revealed a dramatic increased demineralization. Group III disclosed almost typical homogenous surface enamel. elemental analysis showed a highly significant difference between Group III and II and a significant difference between Group III and I. Shear bond strength analysis revealed a significant difference between group I and II and between group III and II. The difference between group III and I was non-significant. Conclusion Both diode laser and nano silver fluoride positively affected dental enamel with the most superior enhancement in enamel criteria was achieved by surface pretreatment by combined nano silver fluoride varnish and diode laser irradiation.